Combined preoperative plasma exchange and red blood cell exchange transfusion in a renal transplant patient with protein S deficiency and hemoglobin SC disease. (June 2022) - Cook, Olivia; Cervi, Andrea; Laureano, Marissa; Gangji, Azim S.; Verhovsek, Madeleine
Abstract: Background: Protein S deficiency is associated with increased risk of venous thromboembolism, complicating the perioperative management of such patients. We present a patient with sickle cell disease (Hb SC genotype) and inherited protein S deficiency who underwent a living-donor renal transplant. To minimize thrombotic risk and sickle cell complications, both plasma exchange and red blood cell (RBC) exchange transfusion were performed pre-operatively. Methods and materials: Plasma exchange was utilized to increase protein S levels and to reduce the risk of post-operative venous thromboembolism, including allograft thrombosis, while RBC exchange was performed to reduce the risk of acute post-operative sickle cell disease complications. Results: With the use of combined pre-operative plasma exchange and RBC exchange transfusion, this patient with protein S deficiency and Hb SC underwent a successful renal transplant without acute sickle cell complications or thrombotic complications. Conclusions: This case demonstrates the potential use of pre-operative plasma exchange in patients with protein S deficiency undergoing high thrombotic risk procedures.